Prevalence of hypercoagulable disorders in inflammatory bowel disease. (March 2014) - Kohoutova, Darina; Pecka, Miroslav; Cihak, Michal; Cyrany, Jiri; Maly, Jaroslav; Bures, Jan
Abstract Objective. Inflammatory bowel disease (IBD) can be associated with hypercoagulable disorders. Aim of this single-center, prospective study was an in-depth evaluation of acquired hypercoagulable states in IBD patients. Methods. A total of 110 patients with Crohn's disease (CD) (aged 19–69; mean 40.5, median 38.5 years), 43 with ulcerative colitis (UC) (aged 17–72; mean 42, median 36 years), and 30 controls were enrolled. Full blood count, serum C-reactive protein (CRP), proteins C and S, activated protein C (APC) resistance, thrombin–antithrombin complex (TAT), F1+F2 fragments, tissue factor pathway inhibitor (TFPI) total and truncated, TFPI-factor Xa, tissue plasminogen activator (tPA) and PAI-I antigen were investigated in peripheral blood samples. Results. Only 18 of 153 (11.8%) IBD patients had hemocoagulation parameters within normal range. Significant difference between IBD patients and controls was found in thrombocyte volume (p < 0.001), protein C (p = 0.025), protein S (p = 0.003), APC resistance (p < 0.001), F1+F2 fragments (p < 0.001), and tPA (p = 0.002). In CD patients who were divided into two subgroups according to serum CRP values (non-active disease: <5 mg/L; active disease ≥5 mg/L), thrombocyte count was significantly lower (p = 0.001), thrombocyte volume was significantly higher (p = 0.002), F1+F2 fragments were significantly lower (p = 0.007) and tPA was significantly higher (p = 0.038) in the subgroup with CRP <5 mg/L. In UC patients, no significant difference depending on CRP was found. Conclusions. Acquired hypercoagulable abnormalities in IBD patients are frequent. Patients with active CD, but not UC, displayed significantly different hemocoagulable parameters, when compared to non-active CD/UC subjects. In patients with active CD (with increased serum CRP concentration) and patients with active extensive UC found at endoscopy (despite low CRP values), prophylactic anticoagulation therapy should be considered.